Iqra Plus Partner Product Development Strategy in Determining the Orientation of Sharia Life Insurance Market Segmentation - Eka Putri Simanjuntak, Febrina; Anggraini, Tuti; Syarbaini, Ahmad Muhaisin B (Manunggal Halim Jaya, 2025)
Mitra Iqra Plus is one of the products owned by PT. Asuransi Jiwa Syariah Bumiputera, Medan Branch, which aims to help fund children's education. The purpose of this study was to determine the development strategy of Mitra Iqra Plus in the orientation of insurance market segmentation at PT. Asuransi Jiwa Syariah Bumiputera, Medan Branch. This type of research uses qualitative research. Data collection techniques include interviews, observations, and documentation. The results of the study indicate that PT Asuransi Jiwa Syariah Bumiputera, Medan Branch is in accordance with sharia elements, namely it does not contain maysir (gambling), gharar (uncertainty), haram, usury, and bathil. The contracts used at Mitra Iqra Plus are Tabarru contracts, Wakalah bil ujrah contracts, and Mudharabah contracts. The marketing strategy chosen is to use a traditional marketing channel strategy through agents. The goal is to provide the best service and satisfaction to prospective customers.